Ivacaftor Inhibits Glioblastoma Stem Cell Maintenance and Tumor Progression - Liu, Kun; Pu, Jun; Nie, Zhi; Shi, Yulin; Jiang, Liping; Wu, Qisheng; Chen, Yongbin; Yang, Cuiping (Frontiers in Cell and Developmental Biology, 2021)
Glioblastoma (GBM) is the most common and malignant primary brain tumor. Glioblastoma stem cells (GSCs) not only initiate and sustain uncontrolled cell proliferation but also resistant to conventional clinical therapies including temozolomide (TMZ) dependent chemotherapy and radiotherapy, implying that there is an urgent need to identify new therapeutic strategies especially specific targeting GSCs. Here, we provide evidence showing that ivacaftor commonly applied in cystic fibrosis therapy acts as a potent inhibitor for GSCs maintenance. We found that ivacaftor promotes cellular apoptosis in vitro and represses patient-derived xenograft (PDX) tumor growth in vivo. In addition, we demonstrate that ivacaftor decreases stemness marker gene expressions of GSCs, including CD133, CD44, and Sox2. In summary, our findings reveal that ivacaftor inhibits glioblastoma progression via specifically eliminating GSCs, which opens a new avenue for GBM clinical therapy in the future.